(untitled) (Zbornik Pravnog fakulteta Sveučilišta u Rijeci, 2022)
A level playing field is enabled when business enterprises can freely compete in the market. However, they cannot compete freely if different rules apply to them. Therefore internationally accepted human rights have to be respected by all business enterprises, no matter their size, sector, ownership and the state of operations. The purpose of the paper is to identify three criteria by which it is possible to achieve a level playing field in business and to examine the criteria using respect for human rights as an example. Using a descriptive method and a method of analysis, the author argues that without the universal minimum standards of respect for human rights a level playing field in business cannot be possible. This will be feasible only with the adoption of a binding international instrument and imposing sanctions on the international level. Consequently, establishing of an international judicial mechanism with a power to sanction corporate human rights abuse is of vital importance.